Optimalisasi Tempat Penyimpanan Terbuka Kendaraan di PT Indonesia Kendaraan Terminal Jakarta - Kencana Verawati; Deri Okta Damawaldi (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of this study was to determine the optimization of vehicle storage in the open yard area at PT. Indonesia Vehicle Terminal (PT. IKT) which is influenced by the zoning policy towards the use of accumulated fields. The method used in this research is a quantitative method in the form of calculating the use of open storage land which is concluded as Yard Occupancy Ratio (YOR). The research data was analyzed by comparing the data before and after the implementation of the zoning system policy at PT. IKT in the period March 2019 - February 2020. The zoning policy has an impact on the amount of loading and unloading production and the capacity of open storage at PT. Indonesia Vehicle Terminal for domestic part. After processing data for the period September 2019 - February 2020, namely September 2019 at 48.63%, October 2019 at 52.39%, November 2019 at 62.75%, December 2019 at 66.75, January 2020 at 76.20% and February 2020 at 82.25%. From YOR which every month the YOR value of PT. IKT has caused open storage fields in the domestic area to overload for storage of CBUs, trucks and heavy equipment. PT. IKT is advised to add new land, especially in the domestic sector, so that operational activities in the terminal are not hampered by the increase in the number of YOR in the domestic field. Otherwise, overbringing costs will arise and increase.